Pengaruh Desain Antarmuka Terhadap Kepuasan Pengguna Pada Aplikasi Fun Murojaah Menggunakan End-User Computing Satisfaction - Sidiq Satria Tama; Arista Pratama; Asif Faroqi (STMIK Budi Darma, 2023)
Nowadays, many Muslims are not interested in reading and memorizing the Al-Qur'an. Therefore, an application is needed that can make it easier for Muslims to read, memorize and repeat this memorization. It is hoped that the Fun Murojaah application will be able to overcome this problem. The Fun Murojaah application is a mobile application that can test or memorize the Al-Qur'an as an effort to increase enthusiasm and development in the Al-Qur'an memorization program. This application is an application to help repeat and improve memorization of the Al-Qur'an in the form of a fun quiz game. So it is hoped that this application can help whenever memorizers of the Al-Qur'an want to try the Al-Qur'an memorization test. The aim of the research is to assess user satisfaction with the application using the End-User Computing Satisfaction (EUCS) method and identify factors that influence user satisfaction. The research began with a literature review and observations to identify problems. The conceptual model was then developed based on previous research, which consists of five variables Content, Accuracy, Format, Ease Of Use, and Timeliness. The sample in the study was 385 users. Questionnaires were developed and distributed to respondents. Data were analyzed using the Structural Equation Model-Partial Least Squares (SEM-PLS) method. The research results show that accuracy, format, and ease of use have a significant influence on user satisfaction with an influence value of 68.6% on user satisfaction and the format has the largest path coefficient value, namely 0.334. The values of the content and timeliness factors are not very significant because the test results have a content value of 0.167 and a timeliness value of 1.692, both of which have low values. The reliability and validity of the measurement instruments were also assessed and were satisfactory. These findings can be used by developers to improve app design and functionality, ultimately improving user experience and satisfaction.